1997
DOI: 10.1016/s0550-3213(97)00576-2
|View full text |Cite
|
Sign up to set email alerts
|

Classical p-branes from boundary state

Abstract: We show that the boundary state description of a Dp-brane is strictly related to the corresponding classical solution of the low-energy string effective action. By projecting the boundary state on the massless states of the closed string we obtain the tension, the R-R charge and the large distance behavior of the classical solution. We discuss both the case of a single D-brane and that of bound states of two D-branes. We also show that in the R-R sector the boundary state, written in a picture which treats asy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
361
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(373 citation statements)
references
References 31 publications
12
361
0
Order By: Relevance
“…This means that the disk one-point function of their vertex operators [31,32] is non vanishing when the disk boundary is attached to such D3-branes. (Indeed in this way or, equivalently, by using the boundary-state formalism [33,34], one can derive the profile for these fields. )…”
Section: Study Of the Back-reactionmentioning
confidence: 99%
“…This means that the disk one-point function of their vertex operators [31,32] is non vanishing when the disk boundary is attached to such D3-branes. (Indeed in this way or, equivalently, by using the boundary-state formalism [33,34], one can derive the profile for these fields. )…”
Section: Study Of the Back-reactionmentioning
confidence: 99%
“…These fluctuations can also be understood as the linear perturbation around the flat spacetime of the following dilatonic gravity 2 in the Einstein frame [6] …”
Section: Jhep11(2002)050mentioning
confidence: 99%
“…The normalization constant N for the static brane is given in [6] from the factorization of the scattering amplitude. Moreover, N = √ π/32 ∼ 10 −2 for d = 26 if we set the string scale 2πl s to 1 and is independent of d t .…”
Section: Jhep11(2002)050mentioning
confidence: 99%
“…A precise relation between such a background and the boundary state has been established in Refs. [6,7]. There it has been shown that if one multiplies the massless tadpoles of |Dp by free propagators and then takes the Fourier transform, one gets the leading term in the large distance expansion of the classical p-brane solutions carrying Ramond-Ramond charges which are non-perturbative configurations of Type II or Type I supergravity.…”
Section: Introductionmentioning
confidence: 99%